A treatment planning comparison of four target volume contouring guidelines for locally advanced pancreatic cancer radiotherapy. - Fokas, E; Eccles, C; Patel, N; Chu, K; Warren, S; Mckenna, W; Brunner, T (2013)
BACKGROUND AND PURPOSE: Contouring of target volumes varies significantly in radiotherapy of pancreatic ductal adenocarcinoma (PDAC). There is a lack of consensus as to whether elective lymph nodes (eLN's) should be included or not in the planning target volume (PTV). In the present study we analyzed the dosimetric coverage of the eLN's and organs at risk (OAR) by comparing four different contouring guidelines. METHODS AND MATERIALS: PTVs were delineated with (Oxford and RTOG guidelines) or without (Michigan and SCALOP guidelines) including the eLNs in eleven patients with PDAC. eLNs included the peripancreatic, paraaortic, paracaval, celiac trunk, superior mesenteric and portal vein clinical target volumes (CTVs). A 3D-CRT plan (50.40 Gy in 28 fractions) was performed to analyze and compare the dosimetric coverage of all eLNs and OAR between the 4 contouring guidelines. RESULTS: The size of Oxford and RTOG PTVs was comparable and significantly larger than the SCALOP and Michigan PTVs. Interestingly the eLNs received a significant amount of incidental dose irradiation by PTV-based plans that only aimed to treat the tumor without the eLNs. The dosimetric coverage of eLN presented a large variability according to the respective contouring methods. The difference in the size of the 4 PTVs was reflected to the dose distribution at the OAR. CONCLUSIONS: Our study provides important information regarding the impact of different contouring guidelines on the dose distribution to the eLNs and the OAR in patients with locally advanced PDAC treated with radiotherapy.